The Role Of The Accounting Profession On The Credibility Of Financial Information - Renny Maisyarah; Dito Aditia Darma Nst; Novi Faurini; Sundari Apriliani; Riza Milianda Kasa; Arwin; Muhammad Irza Aryasta; Fadhlan Fachri (Yayasan Multidimensi Kreatif, 2024)
This study aims to analyze the role of the accounting profession in improving the credibility of financial information. In an increasingly complex and evolving business context, the credibility of financial statements is essential to ensure the trust of investors, stakeholders, and regulators. This study uses a mix methods approach, which is a combination of quantitative methods through surveys and qualitative methods through in-depth interviews and case studies of financial statements from five companies listed on the Indonesian stock exchange during the 2018–2023 period. The results of the study show that the professional competence of accountants, professional ethics, and external audits have a significant influence on the credibility of financial statements. As many as 72% of respondents consider that accountants who have professional certifications, such as CPA or CA, can improve the quality of financial reports. In addition, external audits by big firms (Big Four) and the implementation of strict professional ethics have also been proven to increase the transparency and accuracy of financial statements. Analysis of case studies reveals that companies that implement good accounting standards and involve independent auditors obtain